PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. WILMAR CAHAYA INDONESIA TBK - Sovie Velisa Putri; Anggada Bayu Seta (Jurnal Menara, 2026)
The purpose of this research is to determine the effect of Leadership Style and Work Discipline on Employee Performance both partially and simultaneously at PT. Wilmar Cahaya Indonesia Tbk. This research employs a quantitative method with a descriptive approach. The data collection method used is a questionnaire survey. The data collection includes both primary and secondary data. The sampling technique used is saturated sampling, with a total of 65 respondents. Data analysis is conducted using SPSS version 26. The data analysis techniques used include validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, coefficient of determination testing, and hypothesis testing. In the partial hypothesis testing for the Leadership Style variable (X1), the obtained t-value is greater than the t-table value, which is 4,394 > 2,009, and the significance value is 0,000 < 0,05. This indicates that Leadership Style (X1) has a significant effect on Employee Performance (Y). In the partial hypothesis testing for the Work Discipline variable (X2), the obtained t-value is also greater than the t-table value, which is 6,881 > 2,009, and the significance value is 0,000 < 0,05. This indicates that Work Discipline (X2) has a significant effect on Employee Performance (Y). The coefficient of determination obtained is R Square of 0.470, which means that the variables of leadership style and work discipline influence the employee performance variable by 47%, while the remaining 53% is influenced by other factors not examined in this study.